Dupilumab provides favourable long‐term safety and efficacy in children aged ≥ 6 to < 12 years with uncontrolled severe atopic dermatitis: results from an open‐label phase IIa study and subsequent phase III open‐label extension study. (9th October 2020) - Cork, M.J.; Thaçi, D.; Eichenfield, L.F.; Arkwright, P.D.; Sun, X.; Chen, Z.; Akinlade, B.; Boklage, S.; Guillemin, I.; Kosloski, M.P.; Kamal, M.A.; O'Malley, J.T.; et al.
Summary: Background: Children aged ≥ 6 to < 12 years with severe atopic dermatitis (AD) have limited treatment options. In a 16‐week, randomized, placebo‐controlled, phase III trial in children, dupilumab, a monoclonal antibody inhibiting interleukin (IL)‐4/IL‐13 signalling, significantly improved signs and symptoms with acceptable safety; longer‐term safety and efficacy data are lacking. Objectives: To report the pharmacokinetic profile and long‐term safety and efficacy of dupilumab in children (aged ≥ 6 to < 12 years) with severe AD. Methods: Children (aged ≥ 6 to < 12 years) with severe AD were enrolled in a global, multicentre, phase IIa, open‐label, ascending‐dose, sequential cohort study and subsequent open‐label extension (OLE) study. Patients received single‐dose dupilumab 2 or 4 mg kg −1 followed by 8‐week pharmacokinetic sampling, then 2 or 4 mg kg −1 weekly for 4 weeks (phase IIa), followed by the same weekly regimen (OLE). Primary endpoints were dupilumab concentration–time profile and treatment‐emergent adverse events (TEAEs); secondary assessments included Eczema Area and Severity Index (EASI) and Peak Pruritus Numeric Rating Scale (PP‐NRS) score. Results: Of 38 children enrolled, 37 completed phase IIa and 33 continued to the OLE. Nonlinear, target‐mediated pharmacokinetics characterized dupilumab concentrations (week 24–48 mean serum concentrations: 2 mg kg −1, 61–77 mg L −1 ; 4 mg kg −1, 143–181 mg L −1 ). TEAEs were mostly mild to moderate and transient; none led to treatment discontinuation. The most commonly reported TEAEs were nasopharyngitis (2 mg kg −1, 47%; 4 mg kg −1, 56%) and AD exacerbation (29% and 13%, respectively). Single‐dose dupilumab rapidly improved AD with further improvements through week 52. Mean EASI and PP‐NRS improved by −37%/−33% and −17%/−20% at week 2 (phase IIa) and −92%/−84% and −70%/−58% at week 52 (OLE), respectively. Conclusions: These safety and efficacy results support the use of dupilumab as a continuous long‐term treatment for children aged ≥ 6 to < 12 years with severe AD. Abstract : What is already known about this topic? Severe atopic dermatitis (AD) has a marked negative impact on patient quality of life and can cause financial burden owing to a lack of effective treatments. Dupilumab significantly improved signs and symptoms of AD with an acceptable safety profile in a 16‐week randomized, double‐blind, placebo‐controlled phase III study in children aged ≥ 6 to < 12 years with severe AD. What does this study add? This study extends information on the safety, efficacy and pharmacokinetic profile of dupilumab treatment for up to 52 weeks in children aged ≥ 6 to < 12 years with severe AD. The results support the use of dupilumab as a continuous long‐term treatment for children aged ≥ 6 to < 12 years with severe AD. Linked Comment:  Sibbald. Br J Dermatol 2021; 184 :792–793 .